2022
DOI: 10.1007/s43630-022-00204-4
|View full text |Cite
|
Sign up to set email alerts
|

Light- and pH-dependent structural changes in cyanobacteriochrome AnPixJg2

Abstract: Cyanobacteriochromes (CBCRs) are phytochrome-related photosensory proteins that play an essential role in regulating phototaxis, chromatic acclimation, and cell aggregation in cyanobacteria. Here, we apply solid-state NMR spectroscopy to the red/green GAF2 domain of the CBCR AnPixJ assembled in vitro with a uniformly 13C- and 15N-labeled bilin chromophore, tracking changes in electronic structure, geometry, and structural heterogeneity of the chromophore as well as intimate contacts between the chromophore and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 89 publications
0
12
0
Order By: Relevance
“…Surprisingly, during the first two transitions, the neighboring carbons of rings B (C9) and C (C11) showed only minor Δ δ C changes. It is thus clear that a deprotonation and reprotonation cycle associated with the chromophore (protonation dynamics) in the Meta-R intermediate and subsequent transition, as proposed for both canonical phytochromes 6,13–15 and the red/green CBCR AnPixJg2 31 can be excluded for Slr1393g3, otherwise a drastic Δ δ C change of C9 would be observed. 33,34 Moreover, although it is widely accepted that the isomerization of the C15,C16-double bond is solely linked to the formation of the two primary intermediates, Lumi-R in the forward-reaction and Lumi-G in the backward-reaction, 21 the Δ δ C changes associated with the C15-methine carbon and D -ring carbonyl C19 in the Pr → Lumi-R photoreaction (−0.2 and +0.1 ppm, respectively) are much smaller than those seen in canonical phytochromes, 21 implying that ring D is twisted away from the B – C plane in both states.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Surprisingly, during the first two transitions, the neighboring carbons of rings B (C9) and C (C11) showed only minor Δ δ C changes. It is thus clear that a deprotonation and reprotonation cycle associated with the chromophore (protonation dynamics) in the Meta-R intermediate and subsequent transition, as proposed for both canonical phytochromes 6,13–15 and the red/green CBCR AnPixJg2 31 can be excluded for Slr1393g3, otherwise a drastic Δ δ C change of C9 would be observed. 33,34 Moreover, although it is widely accepted that the isomerization of the C15,C16-double bond is solely linked to the formation of the two primary intermediates, Lumi-R in the forward-reaction and Lumi-G in the backward-reaction, 21 the Δ δ C changes associated with the C15-methine carbon and D -ring carbonyl C19 in the Pr → Lumi-R photoreaction (−0.2 and +0.1 ppm, respectively) are much smaller than those seen in canonical phytochromes, 21 implying that ring D is twisted away from the B – C plane in both states.…”
Section: Resultsmentioning
confidence: 99%
“…In the Pr state, the dynamic nuclear polarization (DNP)-enhanced MAS NMR study of Cph1 has shown that the positive charge is mainly localized at ring B , not spreading over both inner rings as generally assumed. 46 Moreover, the 13 C chemical shifts of the pyrrolic carbons in Cph1 show great similarity to those of AnPixJg2 and the closely related NpR6012g4 in their respective Pr dark states, 18,31,44 suggesting that the electronic structure of the conjugated systems and charge distribution patterns of the Pr chromophores are comparable for all species. These observations imply the migration of partial positive charge into ring C during the Pr → Lumi-R transition.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…7 According to NMR and RR experiments, the PCB chromophore deprotonates either at the ring B or C pyrrole nitrogen, resulting in a tautomeric species where only one proton is shared between these two pyrrole rings. 71,72 In the light of these findings, we assign the 50 µs intermediate to such a deprotonated PCB species.…”
Section: Discussionmentioning
confidence: 92%
“…[65][66][67] Transient de-and re-protonation events are also typical for the photocycle of phytochromes 68,69 , and some studies identified such processes in the red/green CBCR AnPixJ. 70,71 Interestingly, pH-dependent experiments on the same sample indicated that the protonation state of the chromophore has a large affect on the vibrational spectra, but barely affects the visible absorption properties 71,72 , which might explain why the 250 µs process could not be resolved in the transient visible experiments. 7 According to NMR and RR experiments, the PCB chromophore deprotonates either at the ring B or C pyrrole nitrogen, resulting in a tautomeric species where only one proton is shared between these two pyrrole rings.…”
Section: Discussionmentioning
confidence: 99%